ILLOCUTIONARY ACTS UTTERED BY THE CHARACTERS IN TRUE SPIRIT MOVIE - Putri, Riska Anugra; Nur, Sahril; Halim, Nur Mutmainna (Journal of English Literature and Linguistic Studies, 2025)
Human uses language as a tool to communicate with fellow humans. Language serves the purpose of social control to foster good relationship among people. Establishing effective social control is essential for ensuring clear communication and preventing misunderstandings that may lead to conflicts. Consequently, every individual needs to possess the communicative competence to understand expressions within their respective contexts. As it is crucial to understand speech acts and consider the context of utterances. Speech acts are not only observable in daily life, but can also in movies. Movies are forms of literature that can be utilized to explore various studies, including speech acts. One of most frequently occurring speech acts, both in real life and in movies, is illocutionary acts performed by the characters. This thesis focuses on illocutionary acts within character dialogues. In analyzing illocutionary acts, they are not separated from situational context. In this study, the researcher employs Leech’s Speech Situation theory to identify context and Searle’s illocutionary acts theory. To analyze the data, the researcher uses a Pragmatics approach and a descriptive qualitative method. The results are obtained from movie transcripts, which are then interpreted and explained in detail. Based on the findings of the research, there are five types of illocutionary acts uttered by the characters in True Spirit movie. They are assertives, directives, expressives, commisives, and declarations. Among the illocutionary acts, directives are the most commonly used, whereas declaratives are the least frequently employed.